2010
DOI: 10.1021/nl903271d
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Heat Pumping from the Earth Using Surface Phonon Resonant Nanoparticles

Abstract: Nanoparticles that have narrow absorption bands that lie entirely within the atmosphere's transparent window from 7.9 to 13 mum can be used to radiatively cool to temperatures that are well below ambient. Heating from incoming atmospheric radiation in the remainder of the Planck radiation spectrum, where the atmosphere is nearly "black", is reduced if the particles are dopants in infrared transmitting polymers, or in transmitting coatings on low emittance substrates. Crystalline SiC nanoparticles stand out wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
250
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 405 publications
(251 citation statements)
references
References 13 publications
(22 reference statements)
1
250
0
Order By: Relevance
“…Whereas historically radiative cooling was largely developed for night-time applications (1)(2)(3)(4)(5)(6)(9)(10)(11)(12)(13), recent works have achieved daytime radiative cooling (7,14). In particular, it was shown that the radiative cooling to below ambient air temperature can be achieved (7), with a photonic structure that reflects almost all incident sunlight and simultaneously emits significant thermal radiation in the midinfrared.…”
mentioning
confidence: 99%
“…Whereas historically radiative cooling was largely developed for night-time applications (1)(2)(3)(4)(5)(6)(9)(10)(11)(12)(13), recent works have achieved daytime radiative cooling (7,14). In particular, it was shown that the radiative cooling to below ambient air temperature can be achieved (7), with a photonic structure that reflects almost all incident sunlight and simultaneously emits significant thermal radiation in the midinfrared.…”
mentioning
confidence: 99%
“…What such cameras see outdoors for the best cool surfaces is thus almost entirely thermal emission and little reflectance of IR. Sharp absorption peaks in the sky window zone are thus desirable and can be achieved by wellknown dielectric materials in nanoparticle form on metal as we demonstrated in 2010 ( Figure 6) [8]. Polymers that absorb selectively in the sky window band are also useful.…”
Section: Cooling Designs and Angular Responsementioning
confidence: 90%
“…Only then is reduction of P A,DW the best way to maintain net cooling to even lower temperatures. The crossover temperature at which a selective emitter is preferred depends upon heatload, relative surface temperature and environmental conditions [8,39]. Reduction of P A,DW is done using a high IR reflectance outside the sky window and can be angularly enhanced if incoming rays from the lower sections of the sky are reflected or replaced with those from a low E surface.…”
Section: Cooling Designs and Angular Responsementioning
confidence: 99%
See 2 more Smart Citations